CONJOINT ANALYSIS: PRESENTATION OF THE METHOD AND POTENTIAL APPLICATIONS IN HRM RESEARCHE - Chloé GUILLOT-SOULEZ; Sébastien SOULEZ (Revue de Gestion des Ressources Humaines, 2011)
Conjoint analysis is a technique for handling situations in which a decision maker has to deal with options that simultaneously vary across several attributes. Until now it has remained underused in human resource management, although this methodology enables to study the preferences of employees and/or employers confronted with choices in the various areas of HRM. The article first presents the method of conjoint analysis. It then shows its interest and potential applications for researches in human resource management.